Sec-O-glucosylhamaudol suppressed inflammatory reaction induced by LPS in RAW264.7 cells through inhibition of NF-κB and MAPKs signaling. Issue 2 (14th February 2020) - Liu, Guiming; Xie, Jing; Shi, Yurui; Chen, Rongda; Li, Li; Wang, Mengxue; Zheng, Meizhu; Xu, Jiaming
Abstract: As a major bioactive compound from the Saposhnikovia divaricata (Turcz.) Schischk, sec-O-glucosylhamaudol (SOG), has been reported to have anti-nociceptive activity and high 5-lipoxygenase (5-LOX) activity. Nevertheless, the mechanism of the potential anti-inflammatory effects of SOG is unclear. The anti-inflammatory impacts of SOG in RAW 264.7 cell lines stimulated by LPS were explored in the present study. It was found that SOG dose-dependently reduced the emergence of inflammation cytokines, such as IL-6 and TNF-α in Raw264.7 murine macrophages stimulated by LPS. Real-time PCR assay demonstrated the SOG dose-dependently inhibited transcription of these cytokines as well. In addition, it was also found that NF-κB activation and MAPKs phosphorylation including p38, JNK and ERK1/2 induced by LPS were suppressed by SOG. Due to its anti-inflammatory activity, our results suggest that SOG might have therapeutic effects on inflammatory disease, such as acute lung injury or rheumatoid arthritis.